Brand immortality how brands can live long and prosper - Pringle, Hamish. (Gale virtual reference library, 2008)
Explores the key marketing factors in brand health, and shows how brands need to adapt to prosper throughout their life. Shows how to manage strategy to ensure that a brand rides the category life-cycle waves and becomes immortal.